El uso de egodocumentos para los estudios de la América colonial: judeoconversos ante la Inquisición en el siglo XVII - Böttcher, Nikolaus (El Colegio de México, A.C., 2023)
Autobiographical texts, or egodocuments, can be used to obtain information on individual actors and the historical circumstances in which they found themselves through the testimonies they left behind. The complex administration of the Spanish Empire generated an extraordinary wealth of all kinds of egodocuments, written by different actors, such as Spaniards, Indigenous people, mestizos, mulattos and foreigners, both men and women, which provide historians with valuable information for defining and analyzing the protagonists of colonial society. Above all, we have relations of merits, genealogical information and Inquisition records, the last of which form the basis for this article.